Differentiation of body fat composition between skinfold caliper and bioelectrical impedance analysis methods among professors - Leonardo Lubis; Nicole Ngo Zhe Yiin; Dimas Erlangga Luftimas (Bali Anatomy Journal, 2018)
Background: Body fat composition which is reflected by body fat percentage (BF%) is one of the important components in disease risk evaluation. Among the methods available to measure BF%, skinfold calipers (SKF) and bioelectrical impedance analysis (BIA) are the most common used. The study is conducted to observe the difference in body fat composition measurement between skinfold caliper and bioelectrical impedance analysis methods among Professors.Method: This study involved 72 UNPAD Professors (50 ♂, 22 ♀) after fitted into criterias. BF% was measured among UNPAD Professors using SKF and BIA. After obtaining agreement by Bland-Altman Plot, the data was analyzed by muliple paired-t test according to gender, physical activity level and BMI categories. Results: The study showed no significant difference in BF% between SKF and BIA in overall population, between gender and physical activity level (p>0.05). For BMI, the only category that showed significant difference in BF% between the 2 methods is obese I group (p=0.001, p>.05).Conclusions: There is no significant difference between SKF and BIA methods according to gender, physical activity levels and BMI categories except for obese I group.